The Workshop on Making Grobogan Batik as an Effort to Preserve Indonesian Cultural Heritage by KKN UNS in Plosorejo Village, Grobogan: Workshop Pembuatan Batik Grobogan sebagai Upaya Pelestarian Warisan Budaya Indonesia Oleh Kelompok KKN UNS di Desa Plosorejo, Grobogan - Zuhri, Moh Sayful; Sahirul Alim Tri Bawono; Ela Octafiyani; Krisna Amanulloh Adi Wicaksono; Joesephin Dwi Pramesthi; Indah Nurkhasanah; Karlindya Rahma; Mathilda Bella; Kresna Pandu Pratama; Angga Judanto Mahendra; Lukmaniyah Rizky Amalia (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Plosorejo Village in Grobogan is one of the villages that initiated the production of Grobogan batik. However, public awareness and interest are still low, making the potential of batik Grobogan still hampered and has not been able to develop to its full potential. As a form of spreading the impact to the community, KKN Sebelas Maret University students planned a batik program training as a form of community service to the people in Plosorejo. Early planting of the interests and talents of children in Plosorejo can prevent the community from ignoring the community's ignorance of Indonesia's cultural heritage, namely Batik Grobogan. The Grobogan batik Making Training was held to provide opportunities for the people in Plosorejo to preserve the unique culture of Indonesia.